THU0664 Translation, cultural adaptation and validation of the systemic lupus activity questionnaire (SLAQ) in a cohort of italian patients with systemic lupus erythematosus (SLE). (15th June 2017) - Tani, C; Vagelli, R; Carli, L; Stagnaro, C; Drago, F; Lorenzoni, V; Turchetti, G; Mosca, M
Abstract : Background: Evaluation of disease activity is one of the most important assessments in SLE; several instruments have been developed based on clinical and laboratory information recorded by the physician. Patient-administered questionnaires provide useful information with significant time and cost saving. Indeed, patient-reported outcomes are gaining a central role as outcome measures.SLAQ is a patient-reported instrument for the assessment of disease activity in SLE. It consists of three scores: Patient Global Assessment question (PGA) about presence and severity of lupus activity over the past month, questions on 24 symptoms (SLAQscore) and a single Numerical Rating Scale (NRS) for disease activity (0 – 10). Objectives: The aim of the study was to translate and to validate the SLAQ in Italian. Methods: The process of translation and cultural adaptation followed published guidelines (1). The final version of the questionnaire (SLAQit) was pretested in a group of 35 SLE patients to assess acceptability, comprehension and feasibility. The validity of the SLAQit was evaluated by its administering to consecutive SLE patients attending the outpatient's clinic or the inpatients wards. Internal consistency between the three components of the score was evaluated by Chronbach's alpha; the external validity was tested toward validated activity indices (SLEDAI and ECLAM) scored by a physician blinded to the SLAQ results. In a subgroup of 30 patients the questionnaire was administered twice at 2 weeks' interval to assess its reliability. Results: 137 patients were enrolled (92% female, mean age 43.1 years, mean disease duration 15.3 years). At enrollment, the median SLEDAI score was 2 (range 1–18) and 45% of patients had at least one organ damage (median 2, 1–8). The pilot test provided a good acceptability (99.9% of response rate) and feasibility (mean of 4.6±2.3 minutes to be completed, 1–10); moreover, the 100% of patients declared to comprehend the scope of the SLAQ and 67.5% declared no content comprehension problems. Internal consistency was very good between (NRS vs PGA vs SLAQscore (α=0.79). NRS and PGA showed a linear correlation with both ECLAM and SLEDAI scores (ρ=0.24, p=0.004 and ρ=0.45, p<0.001 respectively), while the correlation with the SLAQscore didn't reach the statistical significance. SLAQit showed a very high reliability by comparing the test-retest results (α>0.8 for NRS, PGA and SLAQscore). SLAQit scores resulted directly related to the patients age (p=0.002) and the SLICC score (p=0.003) while no correlation with disease duration was observed. Conclusions: SLAQit demonstrated to be acceptable, comprehensible and feasible in our routine clinical setting; it also showed good internal consistency; correlation with physician's driven instruments is weaker and the SLAQit was influenced by epidemiological and disease-related factors (i.e. damage), thus confirming that the disease perception from the patient's perspective can be different from physicians and influenced by several factors. The SLAQit can be considered a useful screening tool for the first assessment of the disease activity before the standard visit. References: Guillemin F, et al. Journal of Clinical Epidemiology 1993; 46: 1417–1432. Disclosure of Interest: None declared